Macroeconomics Theory, Models & Policy - Curtis, Doug; Irvine, Ian; Open Textbook Library (Open Textbook Library, 2015)
Macroeconomics: Theory, Markets, and Policy provides complete, concise coverage of introductory macroeconomics theory and policy. It examines the Canadian economy as an economic system, and embeds current Canadian institutions and approaches to monetary policy and fiscal policy within that system. The text observes short-run macroeconomic performance, analysis, and policy motivated by the recessions of the early 1980s and 1990s, the financial crisis and recession of 2008-2009, and the prolonged recovery in most industrial countries.A traditional Aggregate Demand and Supply (AD-AS) model is introduced, and a basic modern AD-AS model is developed. Numerical examples, diagrams, and basic algebra are used in combination to illustrate and explain economic relationships. Students learn about: the importance of trade flows, consumption, and government budgets; money supply; financial asset prices, yields, and interest rates; employment and unemployment; and other key relationships in the economy. Canadian and selected international data are used to provide real world examples and comparisons. This text is intended for a one-semester course, and can be used in a two-semester sequence with the companion text, Microeconomics: Markets, Methods, and Models. The three introductory chapters and the International Trade chapter (Chapter 15) are common to both books. This book has been updated and revised by the publisher. A newer adaptation of this book is called Principles of Macroeconomics.
Part One: Introduction -- 1 Introduction to key ideas -- 2 Theories, models and data -- 3 The classical marketplace - demand and supply -- Part Two: Introduction to Macroeconomics -- 4 Economic activity and performance -- 5 Output, business cycles, growth & employment -- 6 Aggregate expenditure & aggregate demand -- 7 The government sector -- Part Three: Financial Markets & Economic Activity -- 8 Money, banking & money supply -- 9 Financial markets, interest rates, foreign exchange rates & AD -- 10 Central banking and monetary policy -- Part Four: Real GDP, Business Cycles, Policy and Growth -- 11 A traditional AD/ AS model -- 12 An AD/ AS model of the inflation rate and real GDP -- 13 Economic growth -- Part Five: International Macroeconomics and Trade Theory -- 14 International Macroeconomics -- 15 International trade
In English.
Description based on print resource
Keywords: Economics -- Textbooks